Antifungal Activity of Extracts from the Antarctic Plant Colobanthus Quitensis Kunth. (Bartl) Cultured in Vitro Against Botrytis Cinerea Pers - Zuniga-Navarro, G; Mendoza-Espinola, L; Mendoza-Espinola, L; Pizarro-Rojas, M; Contreras-Arredondo, R (Taylor and Francis Ltd., 2022)
Botrytis cinerea, a responsible for grey rot that mainly affects fruit and represent a problem in fruit-exporting countries. Synthetic antifungals are used for its control. However, it has developed a specific resistance towards them. Therefore, a search for new natural alternatives that are friendly to the environment has increased in the last decade. In this work, the activity of in vitro-cultured C. quitensis extracts was analysed. Extract was characterized using LC-MS/MS and evaluated in vitro, and in vivo using edible coatings in table grapes. The application of extracts inhibited the development of conidia and mycelium of B. cinerea, with EC50 values of 0.071 ± 0.008 g L−1 and 0.074 ± 0.09 g L−1, respectively, inducing oxidative stress in vitro; on the other hand, in vivo assays showed a protection and preservation of anthocyanins and sugars in table grapes. These results suggest that C. quitensis extracts represent a good alternative to control B. cinerea. © 2022 Informa UK Limited, trading as Taylor & Francis Group.